Instruction of molecular structure similarity and scaffolds of drugs under investigation in ebola virus treatment by atom-pair and graph network: A combination of favipiravir and molnupiravir. (December 2022) - Gider, Veysel; Budak, Cafer
Abstract: The virus that causes Ebola is fatal. Although many researchers have attempted to contain this deadly infection, the fatality rate remains high. The atom-pair fingerprint technique was used to compare drugs suggested for the treatment of Ebola or those that are currently being tested in clinical settings. Subsequently, using scaffold network graph (SNG) methods, the molecular and structural scaffolds of the drugs chosen based on these similar results were created, and the drug structures were examined. Public databases (PubChem and DrugBank) and literature regarding Ebola treatment were used in the analysis. Graphical representations of the molecular architecture and core structures of the drugs with the highest similarity to Food and Drug Administration (FDA)-approved drugs were produced using the SNG method. The combination of molnupiravir, the first licensed oral medication candidate for COVID-19, and favipiravir, employed in other viral outbreaks, should be further researched for treating Ebola, as observed in our study. We also believe that chemists will benefit from understanding the core structure(s) of medication molecules effective against the Ebola virus, their inhibitors, and the chemical structure similarities of existing pharmaceuticals utilized to build alternative drugs or drug combinations. Graphical Abstract: ga1 Highlights: On average, ten years and approximately 2–3 billion dollars are spent to develop a single FDA-approved drug. However, combating sudden global threats like the Ebola epidemic is a very costly and lengthy process. Another way to discover a new drug is to reuse it. To re-use a clinically-trial drug for which the safety risk is already known, it remains only to test and analyze its ability to treat a new disease. The reuse of drugs that had previously been FDA-approved as treatments for EBOLA presents an opportunity for the rapid deployment of effective therapeutics in the current epidemic environment where treatment options are greatly limited. In line with the above-mentioned drug-drug similarity and chemical scaffolds approaches, drugs under investigation in the treatment of Ebola were examined. In this study, the similarity of drugs in the literature for chemical structure similarities with atom pair algorithm was analyzed and examined to find new potential drug candidates that are already approved for the treatment of Ebola or that have passed the clinical trial phase. Then, the similar infrastructure molecules of these similar drugs and the scaffolds for the core molecule were extracted with the Scaffold Network Graph algorithm. Chemists need to know these beforehand. Favipiravir is an effective drug used in the treatment of many viral outbreaks. In the drug-drug similarity analysis procedures and the extraction of scaffolds, results were obtained by taking chemical structure similarities with other drugs using Favipiravir a reference. According to these results, it was observed that Molnupiravir was the drug with the highest similarity to Favipiravir. Considering all these results, we predict that the proposal to use Favipiravir and other drugs under investigation, especially Molnupiravir, which is the first oral drug for COVID-19, can help both clinical and computer analysis processes for use in the treatment of Ebola virus. As a result, the combination of Molnupiravir and Favipiravir, drugs and/or drug candidates currently being studied in clinical trials for the treatment of COVID-19, may form the basis for the design of clinical trials to test the effectiveness of the Ebola virus. Such a combination for the treatment of Ebola can also lead to the adjustment of appropriate dosages and the reduction of the amount of doses administered. The study offers a different approach to Ebola treatment in this aspect.